1995
DOI: 10.1063/1.359465
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress in GaN epitaxial layers grown on sapphire substrates

Abstract: Thermal stress in GaN epitaxial layers with different thicknesses grown on sapphire substrates by metalorganic vapor phase epitaxy using an AlN buffer layer was investigated. Biaxial compressive stress in the GaN layer, due to the difference in the thermal expansion coefficients between GaN and sapphire, was obtained by measuring the curvature of wafer bending, and the observed stress agreed with the calculated stress. In Raman measurements, the E2 phonon peak of GaN was found to shift and broaden with the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(154 citation statements)
references
References 22 publications
10
140
2
1
Order By: Relevance
“…In the present case, the GaN E 2 -high peaks of samples MGS (MOCVD-grown GaN on sapphire), A, B, C, and D were evaluated as 520.7, 569.7, 565.5, 565.7, and 566.3 cm −1 , respectively. Compared to the intrinsic value of 566.8 cm −1 for the stress-free GaN, samples B, C, and D were under tensile stress, while sample A was under compressive stress [36]. This can be due to the rapid release of stress in the nucleation of GaN films during the initial growth by high-temperature (1000 • C) PLD.…”
Section: Resultsmentioning
confidence: 99%
“…In the present case, the GaN E 2 -high peaks of samples MGS (MOCVD-grown GaN on sapphire), A, B, C, and D were evaluated as 520.7, 569.7, 565.5, 565.7, and 566.3 cm −1 , respectively. Compared to the intrinsic value of 566.8 cm −1 for the stress-free GaN, samples B, C, and D were under tensile stress, while sample A was under compressive stress [36]. This can be due to the rapid release of stress in the nucleation of GaN films during the initial growth by high-temperature (1000 • C) PLD.…”
Section: Resultsmentioning
confidence: 99%
“…An additional complication arises for AlGaN grown on sapphire, the most common substrate of choice, as the sapphire (linear thermal expansion coefficient α ~ 7.6x10 -6 k -1 ) exerts a compressive strain to the AlGaN layers (α ~ 5.6x10 -6 k -1 ) during cool down which tends to mask the grown-in tensile strain due to lattice mismatch. Most of the post-growth ex-situ strain characterizations [8][9][10][11][12][13] would in this case measure a combination of a tensile stress due to lattice mismatch and a compressive component due to thermal expansion mismatch. In an attempt to isolate these two competing factors by directly probing the grown-in strain, we have employed an in-situ stress/strain monitor based on wafer-curvature measurement [14].…”
Section: Introductionmentioning
confidence: 99%
“…The observed effects largely overcame the compressive stress resulting from the smaller expansion coefficient of GaN in relation to the sapphire substrate, which has been generally observed on epitaxially grown samples. 56,59,60 In the low temperature range (T s < 500 C), the thicker layers are expected to decrease the "memory" effect of the film-substrate interface, helped by the wider grain boundaries and amorphous regions present.…”
Section: Discussionmentioning
confidence: 99%
“…Differently, in epitaxial GaN, compressive stress generally dominates, because of the larger thermal expansion coefficient of sapphire. 51,[56][57][58][59][60] Large compressive stresses were also reported in films deposited by RF sputtering for substrate temperatures below 500 C. 25 Both the previous literature 39-41,51,52,56,61 and our analysis of the data in the present study indicate that the observed lattice swelling (with changes in both a and c parameters of the GaN hexagonal cell) can be attributed to three main factors: (i) the coalescence/merging of the crystallites/interfaces; 56 (ii) the loss of film material during and after growth; and (iii) impingement of energetic N and the corresponding creation of selfinterstitials. 34,41,52,62,63 These points are discussed in more detail in the following.…”
Section: Discussionmentioning
confidence: 99%